2002
DOI: 10.1139/t02-008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dead loads on the lateral response of battered pile groups

Abstract: The effects of vertical load on the lateral resistance of single piles were initially reviewed to facilitate the interpretation of the test results of pile groups. Then, 18 different lateral load tests were carried out in the centrifuge on the 3 × 3 and the 4 × 4 fixed-head battered pile groups to investigate the effects of vertical load on the group lateral resistance. Vertical dead loads ranging from approximately 20 to 80% of the vertical ultimate group capacity Puv were applied. Based on these tests, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…It can be observed that the increase in the load inclination in both forward and reverse directions results in a reduction in both the pile stiffness and pullout capacity. This influence is similar to that reported for vertical piles [1,3,4,10,17]. pile stiffness and pullout capacity.…”
Section: Pile Displacementsupporting
confidence: 88%
See 1 more Smart Citation
“…It can be observed that the increase in the load inclination in both forward and reverse directions results in a reduction in both the pile stiffness and pullout capacity. This influence is similar to that reported for vertical piles [1,3,4,10,17]. pile stiffness and pullout capacity.…”
Section: Pile Displacementsupporting
confidence: 88%
“…The design of battered piles requires a good understanding of their response to inclined loads, in particular their pullout capacity. This issue was investigated for compressive inclined loads using centrifuge tests [1][2][3][4], which showed that the inclination of both the pile and the load affected the piles bearing capacity. Results indicated that the bearing capacity of a batter pile is less than that of a vertical pile, and that inclination of the load resulted in a decrease in 1278 H. MROUEH AND I. SHAHROUR the bearing capacity of piles.…”
Section: Introductionmentioning
confidence: 99%
“…Other related research on single piles includes (Zhukov andBalov 1978, Zhang et al 1999). Zhang et al (2002) through centrifuge experiments on 3 × 3 and 4 × 4 fixed-head battered pile groups concluded that the effects of vertical load on the lateral resistance of 3 × 3 pile groups were not significant. For 4 × 4 pile groups however, the lateral resistances increased significantly with vertical loads.…”
Section: Introductionmentioning
confidence: 97%
“…For example, Anagnostopoulos and Georgiadis (1993) investigated the interaction among the axial and the lateral responses of piles in clay with model tests. Zhang et al (2002) investigated the effects of the vertical load on the group lateral resistances by centrifuge model test. They pointed out that the influence of the vertical loads is closely linked to the pile-soil system.…”
Section: Introductionmentioning
confidence: 99%